Effect of nocturnal sound reduction on the incidence of delirium in intensive care unit patients: An interrupted time series analysis. (August 2017) - van de Pol, Ineke; van Iterson, Mat; Maaskant, Jolanda
Abstract: Introduction: Delirium in critically-ill patients is a common multifactorial disorder that is associated with various negative outcomes. It is assumed that sleep disturbances can result in an increased risk of delirium. This study hypothesized that implementing a protocol that reduces overall nocturnal sound levels improves quality of sleep and reduces the incidence of delirium in Intensive Care Unit (ICU) patients. Methods: This interrupted time series study was performed in an adult mixed medical and surgical 24-bed ICU. A pre-intervention group of 211 patients was compared with a post-intervention group of 210 patients after implementation of a nocturnal sound-reduction protocol. Primary outcome measures were incidence of delirium, measured by the Intensive Care Delirium Screening Checklist (ICDSC) and quality of sleep, measured by the Richards-Campbell Sleep Questionnaire (RCSQ). Secondary outcome measures were use of sleep-inducing medication, delirium treatment medication, and patient-perceived nocturnal noise. Results: A significant difference in slope in the percentage of delirium was observed between the pre- and post-intervention periods (−3.7% per time period, p = 0.02). Quality of sleep was unaffected (0.3 per time period, p = 0.85). The post-intervention group used significantly less sleep-inducing medication (p < 0.001). Nocturnal noise rating improved after intervention (median: 65, IQR: 50–80 versus 70, IQR: 60–80, p = 0.02). Conclusions: The incidence of delirium in ICU patients was significantly reduced after implementation of a nocturnal sound-reduction protocol. However, reported sleep quality did not improve.